The genetics and neuropathology of Parkinson’s disease - Houlden, Henry; Singleton, Andrew B. (Acta neuropathologica, 2012)
There has been tremendous progress toward understanding the genetic basis of Parkinson’s disease and related movement disorders. We summarize the genetic, clinical and pathological findings of autosomal dominant disease linked to mutations in SNCA , LRRK2 , ATXN2 , ATXN3 , MAPT, GCH1, DCTN1 and VPS35 . We then discuss the identification of mutations in PARK2 , PARK7 , PINK1 , ATP13A2 , FBXO7 , PANK2 and PLA2G6 genes. In particular we discuss the clinical and pathological characterization of these forms of disease, where neuropathology has been important in the likely coalescence of pathways highly relevant to typical PD. In addition to the identification of the causes of monogenic forms of PD, significant progress has been made in defining genetic risk loci for PD; we discuss these here, including both risk variants at LRRK2 and GBA , in addition to discussing the results of recent genome-wide association studies and their implications for PD. Finally, we discuss the likely path of genetic discovery in PD over the coming period and the implications of these findings from a clinical and etiological perspective.